Internalisasi Etika Bermedia Sosial Nahdlatul Ulama dalam Pendekatan Saintifik - Makmun, Ngali Zainal; Mahmudah, Masrurotul; Mushodiq, Muhamad Agus (Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2019)
This study aims to develop ethics in utilizing social media in the style of Nahdlatul Ulama within Scientific Approach in the 2013 National Curriculum. Currently, hoax massively spreads in cyberspace, in which students become some parts of it. Hence, this research is important so that students are able to be more critical in responding to circulated information. This study employs of qualitative research with content analysis approach. Results show that internalization of tabayun principle encourages students not apological and always critical towards information. In addition, this encourages them to extract information which enhances their literacy. The principle of honesty and the usefulness of information also encourage students to be able to process information and communicate the investigation results objectively. In addition, ethics in verbal communication becomes the foundation for students to deliver information in a peaceful way.